MORPHOMETRIC FACTORS OF THE RELIEF AND ESTIMATION OF ALLUVION DRIFTS IN THE BASIN OF LAKE SEVAN (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
In mountainous countries the nature and intensity of most eczogenic geologic processes are determined by many morphometric parameters. Indeed, this state causes the need of morphometric research work in the basin of Lake Sevan. It is a well-known fact that down gradient of the relief influences on the intensity of eczogenic and erosion processes. Rise in down gradient causes activity of plane and linear erosion. The analysis of morphometric and geomorphologic materials showed that the greatest slopes don't have shady ones, but the lighter slopes having intensive folding and activation of eczogenic processes. The tendency of rise in weighted flow is related to the slope increase of mountain rocks as well as anthropogenic load on the landscape. The current ecological state of the Sevan basin requires monitoring and development of protection and improvement strategy of environment.
Keywords: Lake Sevan; linear erosion; eczogenic processes